A Convenient Method for Conversion of Flavonols into Anthocyanins - Elhabiri, Mourad (1995)
Reduction of rutin by zinc amalgam in 3% absolute methanolic hydrochloric acid provides pure 3-O-beta-D-(6”-O-alpha-L-(6'''-deoxy-mannosyl)) glucopyranosyl cyanidin in good yield.